2017
DOI: 10.1037/ccp0000231
|View full text |Cite
|
Sign up to set email alerts
|

Case complexity as a guide for psychological treatment selection.

Abstract: Case complexity as a guide for psychological treatment selection. Journal of Consulting and Clinical Psychology, 85 (9). pp. 835-853. ISSN 0022-006X https://doi.org/10.1037/ccp0000231 eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 54 publications
10
69
1
Order By: Relevance
“…Other studies in primary care services which included HiCBT (among other treatments) have found an upper boundary ranging between 11 and 14 sessions (Howard et al, 1986; Wolgast, Lambert, & Puschner, 2003). As expected, predictors of time‐to‐remission were highly consistent with the prognostic factors highlighted by previous studies in similar services (Delgadillo et al, 2017; Delgadillo, Kellett et al, 2016; Delgadillo, Moreea et al, 2016). LiCBT adequate dose parameters were homogeneous across diagnostic groups; however, patients with social anxiety disorder, OCD and PTSD had poor response rates (<25%).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Other studies in primary care services which included HiCBT (among other treatments) have found an upper boundary ranging between 11 and 14 sessions (Howard et al, 1986; Wolgast, Lambert, & Puschner, 2003). As expected, predictors of time‐to‐remission were highly consistent with the prognostic factors highlighted by previous studies in similar services (Delgadillo et al, 2017; Delgadillo, Kellett et al, 2016; Delgadillo, Moreea et al, 2016). LiCBT adequate dose parameters were homogeneous across diagnostic groups; however, patients with social anxiety disorder, OCD and PTSD had poor response rates (<25%).…”
Section: Discussionsupporting
confidence: 88%
“…However, gradual responders require more sessions to benefit and tend to require HiCBT. Identifying the characteristics of these gradual responders (e.g., more complex cases) could inform the development of stratified models of care, in which such cases are immediately assigned to more intensive/longer treatments (Delgadillo et al, 2017; Delgadillo, Moreea et al, 2016). The case for stratified care is further supported by the present results, since the probability of improvement was comparable between cases that were directly allocated to HiCBT (stratified care) and cases that accessed the full stepped care pathway—which is lengthier and costly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, most of the PAI studies used a prescriptive approach (e.g., DeRubeis et al., ; Huibers et al., ). Others suggested using prognostic models in large observational treatment studies to answer questions concerning personalized predictions (e.g., Delgadillo et al., ; Kessler et al., ). Up to this point, there is no empirical evidence to guide us on the relative strengths, weaknesses, or differences between these modeling strategies.…”
Section: Discussionmentioning
confidence: 99%